Fanfictions na Internet - um clique na construção do leitor-autor - REIS, Fabíola do Socorro Figueiredo dos (Universidade Federal do Pará, 2012)
This study focuses on the presence of the reader-writer of stories created and published on the Internet, more specifically, an author who was once a reader of an original story, and decides to continue it (from the moment which its first original writer finished) or modify it in order to please yourself and/or any other readers, because, as Roland Barthes once said (2004), the writer will always be an imitator of his writings prior to that time, but never original. In the stories created by fans-authors (as the authors committed in the writing of this kind of story are called), we study the modification of the concept of authorship nowadays, because the author loses has a new personality as he/she uses some form of information technology - and now handles with something called hybrid genres: texts that are not just pure, but haven‟t a feature to be defined only by common concepts either. Thus it is difficult to define what is, after all, the author in the era of digital genres. At a time when every day people worldwide increase their number of hours browsing, digital genres represent a new relationship between humans and semiotic instrument, with several aspects to be observed.